Analysis of 3 Idiots Film in Motivating Uninus Students in View from Hypodermic Theory - Dede Deva Permana; Zulfa Saniyyah; Destia Mustikasari (Institute of Computer Science (IOCS), 2022)
This research is a mini research study, which aims to find out the motivation of Uninus students in the second semester of 2020 after watching the movie 3 idiots. This study uses hypodermic needle theory with the definition that the media in this case the film is able to convey ideas and ideas to the audience. The approach used in this study is a qualitative approach, the determination of informants in this study using purposive sampling, namely determining the source as the person who knows best, the sources of data in this study are 30 Uninus students from 7 Universitas Islam Nusantara Study Programs batch 2020. Data collection techniques using online interviews. Based on the results, it can be seen that 30 informants were highly motivated after watching the movie 3 idiots.